iPSCs engrafted in allogeneic hosts without immunosuppression induce donor-specific tolerance to secondary allografts - Tomoki Kamatani; Reiko Kimura; Satoshi Ikeda; Makoto Inoue; Ken-ichiro Seino (Proceedings of the National Academy of Sciences, 2025)
Currently, most cell or tissue transplantations using induced pluripotent stem cells (iPSCs) are anticipated to involve allogeneic iPSCs. However, the immunological properties of iPSCs in an allogeneic setting are not well understood. We previously established a mouse transplantation model of MHC-compatible/minor antigen-mismatched combinations, assuming a hypoimmunogenic iPSC-setting. Here, we found that iPSCs subcutaneously inoculated into MHC-compatible allogeneic host mice resisted rejection and formed teratomas without immunosuppressant administration. Notably, when skin grafts were transplanted onto hosts more than 40 d after the initial iPSCs inoculation, only the skin of the same strain as the initial iPSCs was engrafted. Therefore, donor-specific immune tolerance was induced by a single iPSC inoculation. Diverse analyses, including single-cell RNA-sequencing after transplantation, revealed an increase in regulatory T cell (Treg) population, particularly CD25 + CD103 + effector Tregs within the teratoma and skin grafts. The removal of CD25 + or Foxp3 + cells suppressed the increase in effector Tregs and disrupted graft acceptance, indicating the importance of these cells in the establishment of immune tolerance. Within the teratoma, we observed an increase in TGF-β2 levels, suggesting an association with the increase in effector Tregs. Our results provide important insights for future applications of allogeneic iPSC-based cell or tissue transplantation.